Preparation method of silicon-based negative electrode material

By performing chemical vapor deposition and high-temperature carbon source reaction in porous silica-based materials to form a silicon carbide protective layer, the problem of degradation of battery performance caused by volume expansion during the deintercalation of lithium in the silicon-based negative electrode material is solved, and a silicon-based negative electrode material with high capacity, high first-effect and good cycle performance is achieved.

CN119833592APending Publication Date: 2025-04-15CHANGSHA RES INST OF MINING & METALLURGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411843043.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The volume expansion of existing silicon-based anode materials during the deintercalation of lithium leads to problems such as battery capacity attenuation, reduced Coulomb efficiency and reduced cycle stability.

Method used

Porous silica-based materials are prepared by mixing surfactants, silicate compounds, acids and water, and depositing silicon nanoparticles through chemical vapor deposition in their pores, and finally reacting with trace carbon sources at high temperature to form a silicon carbide protective layer to prepare a silicon-based negative electrode material with excellent pore structure.

Benefits of technology

This method effectively overcomes the volume expansion problem of silicon-based negative electrode material during the deintercalation of lithium, improves the capacity, first-effect and cycling performance of the battery, and meets the use needs of lithium-ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of a silicon-based negative electrode material, which comprises the following steps: (1) uniformly mixing a surfactant, a silicate ester compound, acid and water, continuously stirring to obtain a crystallized substance, drying and roasting to obtain a porous silicon dioxide-based material; (2) crushing the porous silicon dioxide-based material to be micron-sized, contacting the porous silicon dioxide-based material with silane in a fluidized bed, and depositing silicon nanoparticles in pore channels of the porous silicon dioxide-based material through chemical vapor deposition to obtain a silicon-containing precursor; and (3) carrying out contact reaction on the silicon-containing precursor and a trace amount of carbon source, and generating a silicon carbide protection layer on the surface of the silicon-containing precursor to obtain the silicon-based negative electrode material. According to the preparation method of the silicon-based negative electrode material, the silicon-based negative electrode material is obtained by preparing the porous silicon dioxide-based material and performing vapor deposition, so that the silicon-based negative electrode material with stable performance is more favorably obtained, the performance of the material meets the use requirements of a lithium ion secondary battery, and the silicon-based negative electrode material has the characteristics of high capacity, high first efficiency and good circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and in particular relates to a method for preparing a negative electrode material. Background Art

[0002] Recently, with the development of electronic portable devices and electric vehicles, higher requirements have been placed on the volume, weight, capacity and economy of batteries, so there is an urgent need for high energy density batteries.

[0003] Silicon (Si) has the advantages of high theoretical capacity, low lithium deintercalation potential and abundant reserves, and has become the most promising new generation lithium-ion battery negative electrode material. However, silicon will expand by 300% in volume during lithium deintercalation, which will bring a series of adverse effects: such as silicon particle pulverization, electrode structure destruction, repeated expansion and contraction of SEI film leading to battery capacity decay, reduced coulombic efficiency and decreased cycle stability.

[0004] At present, there is technology to compound silicon particles with porous carbon skeletons, and perform chemical vapor deposition of silicon-containing precursors on porous carbon, so that silicon nanoparticles are dispersed in the pore structure of porous carbon. The porous structure in porous carbon can partially buffer the volume effect of silicon in the pores when lithium is inserted and removed, thereby improving the cycle performance of silicon-based negative electrode materials. Facts have proved that this structure has a great improvement in cycle performance compared to silicon-oxygen negative electrode materials. However, the preparation of porous carbon materials requires carbonization and then activation and pore formation by CO2 or water vapor. The activation and pore formation process has strict requirements, and the performance of the pore-forming materials is prone to instability. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a method for preparing a silicon-based negative electrode material with high capacity, high initial efficiency and good cycle performance.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a silicon-based negative electrode material comprises the following steps: (1) uniformly mixing a surfactant, a silicate compound, an acid and water, continuously stirring to obtain a crystallized product, and then drying and calcining to obtain a porous silica-based material; (2) crushing the porous silica-based material to micrometer scale, contacting it with silane in a fluidized bed under an inert atmosphere, and depositing silicon nanoparticles in the pores of the porous silica-based material by chemical vapor deposition to obtain a silicon-containing precursor; (3) The silicon-containing precursor is contacted with a trace amount of carbon source to react, thereby generating a silicon carbide protective layer on the surface of the silicon-containing precursor to obtain the silicon-based negative electrode material.

[0007] In the above preparation method, preferably, the surfactant is surfactant P123, the silicate compound is tetraethyl orthosilicate, and the acid includes one or more of hydrochloric acid, phosphoric acid, boric acid and nitrous acid. The use of this surfactant is conducive to the preparation of porous silica-based materials with excellent pore structure. During the reaction and carbonization stage of tetraethyl orthosilicate, the organic components of the ester will volatilize to form pores, and the remaining Si-O elements will remain to form a skeleton structure. By cooperating with surfactant P123 and the subsequent specific preparation process, it is conducive to obtaining a porous silica-based material with excellent pore structure.

[0008] In the above preparation method, preferably, the molar ratio of the surfactant, silicate compound, acid and water is (0.015-0.019):1:(3-6):(40-60). More preferably, the molar ratio of the surfactant, silicate compound, acid and water is 0.017:1:5:50. Our research shows that the amount of surfactant and acid will affect the generation rate of silica and the generation of pore structure. The control of the above molar ratio is conducive to the generation of solid-phase silica with excellent pore structure, and then through subsequent low-temperature pretreatment, a matrix material with better pore structure can be obtained.

[0009] In the above preparation method, preferably, the continuous stirring to obtain the crystallized product is to react the reaction system at 80-100° C. for 20-30 hours. The above reaction conditions are conducive to the generation of porous silicon dioxide.

[0010] In the above preparation method, preferably, after continuous stirring to obtain a crystallized product, the solid phase is separated, the solid phase is placed in a closed environment, and pretreated at 100°C for 20-30 hours, and the solid phase is kept in a shaking state during the pretreatment process. This process can adjust the pore structure of the solid phase, and is also equivalent to a supplement to the crystallization process, which is conducive to obtaining a porous silica-based material with better structural properties.

[0011] In the above preparation method, preferably, the calcination temperature is 520-570°C, and the calcination time is 5-7h. More preferably, the calcination temperature is 550°C, and the calcination time is 6h.

[0012] In the above preparation method, preferably, the porous silica-based material is crushed to a D50 of 7.5±1.0 um. Crushing the above micron-sized porous silica-based material is beneficial to the loading of silicon, and the micron-sized material can also be directly used as a negative electrode material without being loaded on other materials.

[0013] In the above preparation method, preferably, the temperature of chemical vapor deposition is 570-620°C, the time is 28-34h, the atmosphere of chemical vapor deposition is SiH4-N2 mixed gas, and the volume concentration of SiH4 is 15-25%. More preferably, the temperature of chemical vapor deposition is 600°C, the atmosphere of chemical vapor deposition is SiH4-N2 mixed gas, and the volume concentration of SiH4 is 20%. The above chemical vapor deposition conditions are conducive to uniform deposition of silicon particles in porous silica-based materials.

[0014] In the above preparation method, preferably, when the silicon-containing precursor is contacted with a trace carbon source for reaction, the carbon source is acetylene, and the silicon-containing precursor is passed through a continuous feeding high-temperature CVD furnace with a nitrogen atmosphere at a feeding rate of 100g / min, and acetylene gas is introduced during the feeding process, and the acetylene gas introduction flow rate is 0.05-0.1L / min. In the process of depositing silicon in the original gas phase deposition silicon process, it is inevitable that silicon nanoparticles will remain on the surface of micron particles, and silicon nanoparticles will expand and fall off, resulting in a decrease in battery performance. By adding a trace carbon source at high temperature, the surface silicon nanoparticles can be reacted to form silicon carbide, which does not participate in the later battery reaction and is in a combined state with the original particles, thereby optimizing the material performance.

[0015] In the above preparation method, preferably, the reaction temperature when the silicon-containing precursor contacts and reacts with a trace amount of carbon source is 1030-1100°C.

[0016] The method for preparing the silicon-based negative electrode material of the present invention more specifically comprises the following steps: (1) After dissolving the surfactant material and an appropriate amount of water, add a silicate compound and an appropriate amount of acid (hydrochloric acid, phosphoric acid, boric acid, nitrous acid, etc. or a mixture thereof), mix them evenly, and continuously stir to obtain a crystallized product. After pretreatment at 100°C, wash with water, dry, and carbonize, a porous silica-based material can be obtained. The porous silica-based material has silicon and oxygen as the main elements, and is compounded with other elements such as C, P, N, and B to improve conductivity.

[0017] (2) The porous silica-based material is crushed to the micron level to obtain a material of suitable particle size.

[0018] (3) In a N2 fluidized bed, silane is brought into contact with a porous silica-based material, and silicon nanoparticles are deposited in the pores of the porous silica-based material through high temperature reaction and chemical vapor deposition.

[0019] (4) The obtained material is then subjected to high temperature and reacts with a trace amount of carbon source to form a silicon carbide protective layer, thereby obtaining a silicon-based negative electrode material.

[0020] Compared with the prior art, the advantages of the present invention are: The method for preparing the silicon-based negative electrode material of the present invention prepares a porous silica-based material by a new method, then vapor deposits silicon, and finally generates silicon carbide by reacting the silicon on the surface of the material with a carbon source to obtain a silicon-based negative electrode material. This is more conducive to obtaining a silicon-based negative electrode material with stable performance, and the material performance meets the requirements of lithium-ion secondary batteries, and has the characteristics of high capacity, high initial efficiency, and good cycle. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0022] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0024] Embodiment 1: A method for preparing a silicon-based negative electrode material comprises the following steps: (1) The surfactant P123 was dissolved in an appropriate amount of deionized water, and tetraethyl orthosilicate and hydrochloric acid were added thereto, wherein the molar ratio of P123:tetraethyl orthosilicate:hydrochloric acid:water was 0.017:1:5:50. The above mixture was stirred and mixed continuously at 100°C for 24 hours to obtain a crystallized product (complete reaction). The solid phase was separated and pretreated at 100°C for 30 hours in a closed environment, washed with deionized water until neutral, and then dried at 100°C for 3 hours. The mixture was placed in a calcining furnace and heated to 550°C at 5°C / min for calcining for 6 hours to obtain a porous silica-based material.

[0025] (2) The obtained porous silica-based material is crushed to a median particle size D50: 7.5±1.0um, and the test ratio is 700-1000m 2 / g range.

[0026] (3) Silicon deposition: The obtained material is placed in a fluidized bed, and the temperature is raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere, and then a 20% SiH4-N2 mixed gas is introduced, and the temperature is maintained at 600°C in the 20% SiH4-N2 mixed atmosphere for 30 hours to perform silicon deposition; then the temperature is naturally lowered under the protection of N2; (4) 1 kg of the material obtained in step (3) is rapidly passed through a high-temperature CVD furnace with a nitrogen atmosphere at a certain angle at a rate of 100 g / min, the temperature of which is 1050° C. During the passage, a trace amount of acetylene organic gas of 0.1 L / min is introduced. The passage time of all the material is set to 10 min. The silicon atoms on the surface of the material react with the decomposed carbon to form a silicon carbide protective layer on the surface. The material passes through the CVD furnace outlet and rapidly enters a nitrogen atmosphere low-temperature cooling tank to obtain a silicon-based composite material. The silicon content in the silicon-based composite material is 48.4 wt %, and the median particle size D50 is 9 μm.

[0027] Embodiment 2: A method for preparing a silicon-based negative electrode material comprises the following steps: (1)-(2) are the same as (1)-(2) in Example 1.

[0028] (3) Silicon deposition: The obtained mixed material is placed in a fluidized bed and heated from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. Then, a 20% SiH4-N2 mixed gas is introduced and the temperature is maintained at 600°C for 32 h in a 20% SiH4-N2 mixed atmosphere to carry out silicon deposition. Thereafter, the temperature is naturally lowered under the protection of N2.

[0029] (4) 1 kg of the material obtained in step (3) is rapidly passed through a high-temperature CVD furnace with a nitrogen atmosphere continuously fed at a certain angle at a rate of 100 g / min, the temperature of which is 1050°C. During the passage, a trace amount of acetylene organic gas of 0.1 L / min is introduced. The passage time of all the material is set to 10 min. The silicon atoms on the surface of the material react with the decomposed carbon to form a silicon carbide protective layer on the surface. The material passes through the CVD furnace outlet and rapidly enters a nitrogen atmosphere low-temperature cooling tank to obtain a silicon-based composite material. The silicon content in the silicon-based composite material is 49.7 wt %, and the median particle size D50 is 9 μm.

[0030] Embodiment 3: A method for preparing a silicon-based negative electrode material comprises the following steps: (1)-(2) are the same as (1)-(2) in Example 1.

[0031] (3) Silicon deposition: The obtained mixed material is placed in a fluidized bed and heated from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. Then, a 20% SiH4-N2 mixed gas is introduced and the temperature is maintained at 600°C in a 20% SiH4-N2 mixed atmosphere for 34 h to carry out silicon deposition. Thereafter, the temperature is naturally lowered under the protection of N2.

[0032] (4) 1 kg of the material obtained in step (3) is rapidly passed through a high-temperature CVD furnace with a nitrogen atmosphere continuously fed at a certain angle at a rate of 100 g / min, the temperature of which is 1050°C. During the passage, a trace amount of acetylene organic gas of 0.1 L / min is introduced. The passage time of all the material is set to 10 min. The silicon atoms on the surface of the material react with the decomposed carbon to form a silicon carbide protective layer on the surface. The material passes through the CVD furnace outlet and rapidly enters a nitrogen atmosphere low-temperature cooling tank to obtain a silicon-based composite material. The silicon content in the silicon-based composite material is 50.3 wt% and the median particle size D50 is 9 μm.

[0033] Embodiment 4: A method for preparing a silicon-based negative electrode material comprises the following steps: (1) The surfactant P123 was dissolved in an appropriate amount of deionized water, and tetraethyl orthosilicate and hydrochloric acid were added thereto, wherein the molar ratio of P123:tetraethyl orthosilicate:hydrochloric acid:water was 0.017:1:5:50. The above mixture was stirred and mixed continuously at 100°C for 24 hours to obtain a crystallized product (complete reaction). The solid phase was separated, washed with deionized water until neutral, and then dried at 100°C for 3 hours. The mixture was placed in a calcining furnace and heated to 550°C at 5°C / min for calcining for 6 hours to obtain a porous silica-based material.

[0034] (2) The obtained porous silica-based material is crushed to a median particle size D50: 7.5±1.0um, and the test ratio is 700-1000m 2 / g range.

[0035] (3) Silicon deposition: The obtained material is placed in a fluidized bed, and the temperature is raised from room temperature to 600°C at a rate of 2°C / min in a N2 atmosphere. Then, a 20% SiH4-N2 mixed gas is introduced and the temperature is maintained at 600°C in the 20% SiH4-N2 mixed atmosphere for 30 h to carry out silicon deposition; thereafter, the temperature is naturally lowered under the protection of N2.

[0036] (4) 1 kg of the material obtained in step (3) is rapidly passed through a high-temperature CVD furnace with a nitrogen atmosphere at a certain angle and a continuous feed rate of 100 g / min at a temperature of 1050° C. During the passage, a trace amount of acetylene organic gas of 0.1 L / min is introduced. The passage time of all the materials is set to 10 min. The silicon atoms on the surface of the material react with the decomposed carbon to form a silicon carbide protective layer on the surface. The material passes through the CVD furnace outlet and rapidly enters a nitrogen atmosphere low-temperature cooling tank to obtain a silicon-based composite material. The silicon content in the silicon-based composite material is 47.6 wt %, and the median particle size D50 is 9 μm.

[0037] Table 1 is a comparison result of the first efficiency of the silicon-based composite materials obtained in the above embodiments. The test method is as follows: (1) The silicon-based composite material obtained in the embodiment is mixed with water according to the ratio of silicon-based composite material: binder: conductive agent of 5:2:3. After mixing and stirring, button cells are prepared on the coating film. The test is carried out by 0.1C charge and discharge to test the capacity and first efficiency of the test material.

[0038] Table 1: Performance data of the silicon-based composite materials prepared in the examples

[0039] Table 2 shows the cycle performance comparison results of 18650 cylindrical batteries prepared by mixing the precursors obtained in the above embodiments with graphite. The test method is as follows: (1) The silicon-based composite material obtained in the embodiment is uniformly mixed with graphite at a ratio of 1:10; (2) The mixed material is prepared into a cylindrical battery and subjected to a 0.5C charge / 1C discharge cycle test.

[0040] Table 2: Performance data of silicon-based composite materials prepared in the examples

Claims

1. A method for preparing a silicon-based negative electrode material, characterized in that: The following steps are involved: (1) uniformly mixing a surfactant, a silicate compound, an acid and water, continuously stirring to obtain a crystallized product, and then drying and calcining to obtain a porous silica-based material; (2) crushing the porous silica-based material to micrometer scale, contacting it with silane in a fluidized bed under an inert atmosphere, and depositing silicon nanoparticles in the pores of the porous silica-based material by chemical vapor deposition to obtain a silicon-containing precursor; (3) The silicon-containing precursor is contacted with a trace amount of carbon source to react, thereby generating a silicon carbide protective layer on the surface of the silicon-containing precursor to obtain the silicon-based negative electrode material.

2. The preparation method according to claim 1, characterized in that: The surfactant is surfactant P123, the silicate compound is ethyl orthosilicate, and the acid includes one or more of hydrochloric acid, phosphoric acid, boric acid and nitrous acid.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the surfactant, silicate compound, acid and water is (0.015-0.019):1:(3-6):(40-60).

4. The preparation method according to claim 1, characterized in that: The crystallized product is obtained by continuous stirring and the reaction system is reacted at 80-100° C. for 20-30 hours.

5. The preparation method according to claim 1, characterized in that: After continuous stirring to obtain a crystallized product, the solid phase is separated, the solid phase is placed in a closed environment, and pretreated at 100° C. for 20-30 hours. During the pretreatment, the solid phase is kept in a shaking state.

6. The preparation method according to claim 1, characterized in that: The calcination temperature is 520-570° C. and the calcination time is 5-7 hours.

7. The preparation method according to claim 1, characterized in that: The porous silica-based material was crushed to a D50 of 7.5±1.0 um.

8. The preparation method according to claim 1, characterized in that: The temperature of chemical vapor deposition is 570-620° C., the time is 28-34 hours, the atmosphere of chemical vapor deposition is SiH4-N2 mixed gas, and the volume concentration of SiH4 is 15-25%.

9. The preparation method according to claim 1, characterized in that: When the silicon-containing precursor is contacted with a trace carbon source for reaction, the carbon source is acetylene, and the silicon-containing precursor is passed through a continuous feeding high-temperature CVD furnace with a nitrogen atmosphere at a feeding rate of 100 g / min. Acetylene gas is introduced during the feeding process, and the flow rate of acetylene gas is 0.05-0.1 L / min.

10. The preparation method according to claim 9, characterized in that: The reaction temperature when the silicon-containing precursor contacts and reacts with a trace amount of carbon source is 1030-1100°C.